1984
DOI: 10.1002/j.1537-2197.1984.tb14173.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Morphology of an Iron Plaque on the Roots of Typha Latifolia L. Grown in Solution Culture

Abstract: Roots of Typha latifolia L. exposed to Fe 2 + under reduced conditions in solution culture developed visible coatings (plaques) of an oxidized Fe compound that extended as much as 15-17 /tm into the rhizosphere. Iron concentrations were significantly less and discoloration was not apparent on the surface of roots exposed to Fe-(BPDSh, Fe>, Fe-EDDHA, and Fe-EDT A. The extent of plaque formation increased with the concentration of Fe 2 + in solution and with pH of the solution in the range of 3.0 to 4.6. Above p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
70
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 20 publications
8
70
1
Order By: Relevance
“…of wetland plants are known to form so-called iron Tolerance of wetland plants to high ferrous iron plaque on their roots by oxidizing Fe^"^ to Fe^"^ concentrations is associated with oxidation in the resulting from the oxidizing activity of the plant rhizosphere (Bartlett, 1961;Green & Ftherington, roots and associated micro-organisms (Chen, Dixon 1977;Johnson-Green & Crowder, 1991;Wang & & Turner, 1980;Mendelssohn & Postek, 1982;Peverly, 1996). Oxidation in the rhizosphere might Taylor, Crowder & Rodden, 1984;McLaughlin, van also diminish the toxicity of other reduced subLoon & Crowder, 1985;Conlin & Crowder, 1989; stances such as Mn^+ and S'^" (Armstrong, 1967;Otte et al, 1989;St-Cyr & Crowder, 1990;Crowder Chen et al, 1980;Armstrong, Brandle & Jackson, & St-Cyr, 1991). Recently, with reference to the 1994; Smolders & Roelofs, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…of wetland plants are known to form so-called iron Tolerance of wetland plants to high ferrous iron plaque on their roots by oxidizing Fe^"^ to Fe^"^ concentrations is associated with oxidation in the resulting from the oxidizing activity of the plant rhizosphere (Bartlett, 1961;Green & Ftherington, roots and associated micro-organisms (Chen, Dixon 1977;Johnson-Green & Crowder, 1991;Wang & & Turner, 1980;Mendelssohn & Postek, 1982;Peverly, 1996). Oxidation in the rhizosphere might Taylor, Crowder & Rodden, 1984;McLaughlin, van also diminish the toxicity of other reduced subLoon & Crowder, 1985;Conlin & Crowder, 1989; stances such as Mn^+ and S'^" (Armstrong, 1967;Otte et al, 1989;St-Cyr & Crowder, 1990;Crowder Chen et al, 1980;Armstrong, Brandle & Jackson, & St-Cyr, 1991). Recently, with reference to the 1994; Smolders & Roelofs, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Typha latifolia L. is a common and productive wetland plant of world-wide geographical distribution. It can colonize metal-contaminated areas (McNaughton et al, 1974;Taylor & Crowder, 1983a;Ye et al, 1997) and produce iron plaque under field and in culture solution conditions (Taylor et al, 1984;Crowder et al, 1987;Ye, Baker & Wong, 1994). The experiments presented here aimed to determine the effect of iron plaque on growth and copper (Cu) and nickel (Ni) immobilization, accumulation and tolerance in T. latifolia.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the roots of reeds grown in solutions with low levels of metals (LM) accumulated 6.81±1.47 mg/g Ba, while the roots in solutions with high level of metals (HM) sequestered 12.26±3.14 mg/g Ba after one week. This is not surprising as previous research also indicated that accumulation of metals in plants was correlated with concentrations in substrate [31]. Deng et al [32] also stated that the concentration of metals in the underground tissues of wetland plants showed strong positive correlations with the levels of elements in sediment.…”
Section: Resultsmentioning
confidence: 71%
“…Hydrous iron oxide (Fe-plaque) is commonly formed on the surfaces of roots of wetland plants, such as rice (Oryza sativa L.), Typha latifolia, and Phragmites communis, and is mainly caused by the oxidation of ferrous iron and the precipitation of iron oxide on the root surface and rhizosphere (Taylor and Crowder 1983;Taylor, Crowder, and Rodden 1984;Zhou, Shi, and Zhang 2007). In anaerobic conditions, rice roots release oxygen to the rhizosphere that results in the formation of Fe-plaque on the surface of the roots (Armstrong 1967;Chen, Dixon, and Turner 1980).…”
Section: Introductionmentioning
confidence: 99%